2008
DOI: 10.1071/sr07220
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of continuous and time-controlled grazing systems on soil characteristics in Southeast Queensland

Abstract: Grazing by livestock has a great influence on soil characteristics with major effects on soil carbon and nitrogen cycling in grazing lands. Grazing practices affect soil properties in different ways depending on the prescribed stocking rate and grazing periods. The new grazing system of short, intensive grazing followed by a long period of rest, referred to as time-controlled grazing (TC grazing), has become popular among many graziers in Australia and elsewhere. However, little research has been carried out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 40 publications
2
52
0
2
Order By: Relevance
“…It typically increases ground cover, litter cover, and the cover of economically desirable pasture species (40,41), and it facilitates improved water infiltration (42). It also can have benefits for microarthropods (43) and for soil chemistry, leading to reduced nitrate and phosphorus levels (41). Despite these benefits, fast-rotational grazing has limitations (44), and like all grazing systems, it depends on appropriate management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…It typically increases ground cover, litter cover, and the cover of economically desirable pasture species (40,41), and it facilitates improved water infiltration (42). It also can have benefits for microarthropods (43) and for soil chemistry, leading to reduced nitrate and phosphorus levels (41). Despite these benefits, fast-rotational grazing has limitations (44), and like all grazing systems, it depends on appropriate management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…However, in south-east Queensland, Sanjari et al (2008) found that, compared with continuous grazing, time-control grazing decreased extractable soil P. While it has been claimed that short duration grazing systems can increase stocking capacity of rangelands, a study over 5 years in Wyoming found no effect on daily weight gains whereas increases in stocking rate could only be achieved with unacceptably high risks of deterioration of the rangelands (Hart et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…They therefore chose to explore various technologies, including grazing management, within whole-farm scenarios. Second, they decided that the control grazing system would not be the 'continuous grazing' used by many other investigators (Earl and Jones 1996;Garden et al 2000;Waller et al 2001;Dowling et al 2005;Sanjari et al 2008) as it is rarely practised by commercial livestock producers on the Northern Tablelands. Thus, the treatment chosen to represent typical grazing management practice in the region, was flexible rotational grazing over a moderate number of paddocks with relatively long graze periods and short rest periods.…”
Section: Introductionmentioning
confidence: 99%
“…Grazing has been shown to increase carbon storage in C4-dominated grasslands (Sanjari et al 2008), whereas grazing decreased soil organic carbon in C3-dominated grasslands (Li et al 2008). It has been suggested that changes in plant species composition as a result of grazing may be more important than direct or indirect effects of grazing on soil carbon (Yates et al 2000).…”
Section: Grazing Pressurementioning
confidence: 99%